The concepts of the media about teaching/learning English: an analysis of media discourse - Hornick, Carmen (2006)
The aim of this paper is to discuss the process of building common sense theories about teaching and learning English as a second language in Brazil. From a discursive analytical perspective, this work observes the phenomenon through the discourse of a weekly magazine called Veja. In the 1980s, the necessity of leaning English as a second language was largely spread by the media and, consequently, its concepts about a better way to learn as well. Through the analysis of linguistic aspects, this article aims to understand the discursive heterogeneity that builds such discourse in order to grasp the understanding of the phenomenon.